Directions of the development of the Kiev municipal consultative diagnostic centers in new economic conditions - Kravchenko, V. V. (Journal of Education, Health and Sport, 2017)
Background Improving of the outpatient care is an urgent problem of the health care system inUkraine. Objective: to determine the problems of organizing of the Consultative and Diagnostic Centers (CDCs) in Kiev, to consider the foreign experience of forming a partnership between the state and the private sector in health care and to determine the direction of development of the CDCs. Materials and methods. Priority directions for the development of communal CDCs in the current economic conditions were substantiated using the system approach and analysis method, as well as the information-analytical method. The information base for their formation were the scientific works of Ukrainan and foreign specialists in public-private partnership (PPP) and management, as well as the results of own studies. Sociological survey of 437 patients and 411 physicians of communal CDCs and an expert assessment of the state, problems of the organization and prospects for further development of communal CDCs (by 21 highly qualified specialists in the organization and management of public health) were conducted in2017 in Kiev. Results It is established that the population and physicians are dissatisfied with the existing organization of the CDC’s work. The results of the expert evaluation also demonstrated the existence of a number of organizational problems in the CDCs. It is determined that the development of the CDCs depends on financing and management, the introduction of mechanisms of public-private partnership. The necessity of reorganizing and improving the management of the CDCs is substantiated. Conclusions Formation of the economic mechanism of the CDCs on the principles of public-private partnership and the preparation of modern managers for the management of the CDCs are the priority directions of development of communal CDCs in current conditions.